PENGARUH FINANCIAL DISTRESS, CORPORATE SOCIAL RESPONCIBILITY, DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE - Juni Elfrida Telaumbanua (Yayasan Kayyis Mulia Jaya, 2026)
The purpose of this study was to determine the effect of Financial Distress, Corporate Social Responsibility, and Capital Intensity on Tax Avoidance, both partially and simultaneously. This study was conducted at the Indonesia Stock Exchange (IDX). The population consisted of food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2025. A total sample of 9 companies was obtained, resulting in 45 data points from the purposive summation technique. The data analysis method used was descriptive statistics. The results of this study indicate that Financial Distress, Corporate Social Responsibility, and Capital Intensity simultaneously influence Tax Avoidance. Financial Distress partially influences Tax Avoidance, Corporate Social Responsibility partially influences Tax Avoidance, and Capital Intensity partially influences Tax Avoidance. Keywords: Financial Distress, Corporate Social Responsibility, Capital Intensity, Tax Avoidance.